Lexical and structural ambiguity in Treasure Island" by Robert Louis Stevenson - Nguyễn, Diệu Linh (University of Languages and International Studies, 2017)
Ambiguity is one of the interesting aspects of language. Not only can it make interlocutors or readers misunderstand but it is also an effective tool to make literature works attractive. Therefore, it has received many concerns from linguists. This study i (...)